Environment education: A first step in solving plastic pollution - Liu, Jianli; Hu, Zhubing; Du, Fangfang; Tang, Wei; Zheng, Siting; Lu, Shanzhou; An, Lihui; Ding, Jiannan (Frontiers in Environmental Science, 2023)
Plastic pollution has been today’s most highly visible environmental problem in the world. How to responsibly manage plastic waste to control and eliminate plastic pollution has been a global challenge. We have begun to address these issues and developed some science-based solutions and emerging technologies. However, tackling such an intractable challenge requires systematic solutions except for science-based and technology-based ones. Environmental education, fostering plastic pollution prevention within society’s educational system, will provide a powerful and feasible pathway at a low cost. Within this perspective, the value and the way forward of education in solving plastic pollution are primarily discussed. Environmental education, including school-level education for students, sustainable consumption behavior guidance, and pollution prevention education for the public, is the feasible, effective, and permanent resolution of plastic pollution in the future.